1992
DOI: 10.1177/019459988910700609.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of early otorrhea in ventilation tubes

Abstract: The incidence of early postoperative otorrhea after placement of ventilation tubes ranges from 12% to 40%. This prospective randomized study of 430 children, ages 6 months to 15 years, examined the efficacy of sulfacetamide/prednisolone otic drops used for 3 days postoperatively in reducing the incidence of otorrhea at 1 week after the placement of Donaldson tubes. Subjects were randomized into two groups--drops and no drops. Preoperative diagnosis and intraoperative findings were correlated with findings. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…In this study, the patient discharge rate was 14.29% which is in keeping with other reports on postgrommet otorrhoea [2,5,9]. Four of the five ears which developed discharge had thick mucoid effusions at myringotomy, the remaining one having had a thin serous effusion (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the patient discharge rate was 14.29% which is in keeping with other reports on postgrommet otorrhoea [2,5,9]. Four of the five ears which developed discharge had thick mucoid effusions at myringotomy, the remaining one having had a thin serous effusion (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies on these associations often used univariable analyses or included a small selection of predictors [7], [12]–[14], [17], [18]. To account for dependencies between predictors, we have performed a multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We selected candidate predictors based on their suggested or shown association with OM or TTO in the literature (see table 1 for definitions) [7][10], [12]–[15], [17], [18]. First, we assessed the relation between each of the candidate predictors and our main outcome (one or more episodes of TTO in the time period since tympanostomy tube placement).…”
Section: Methodsmentioning
confidence: 99%
“…A distinction should be made between early otorrhea, which appears within 2-4 weeks after the operation, and delayed otorrhea, which occurs several months postoperatively [40]. The prevalence of early otorrhea ranges from 10 to 20% [4,5,19,22,26,36,57,65,66,81], whereas delayed otorrhea seems to be more frequent, occurring in 26% of cases [36]. Other studies have reported even higher rates of otorrhea, up to 50% of cases within a 3-year observation period [41,42] and even 83% in a study on children up to 36 months old at the time of insertion.…”
Section: Otorrheamentioning
confidence: 99%
“…The routine perioperative prophylactic use of local antibiotic ear drops flies in the face of evidence-based [19,66,81] A related meta-analysis found an 85% reduction of otorrhea when perioperative antibiotic drops were used [21], but the low incidence of this complication and the heterogeneity of the published studies prevented the authors from drawing a final conclusion; they therefore recommended the judicious use of these agents, with emphasis on those cases at higher risk of otorrhea, namely those with mucoid or purulent effusion. In terms of preventing biofilm formation, emphasis has been placed on the effect of a surface treatment of fluoroplastic grommets.…”
Section: Otorrheamentioning
confidence: 99%